KOMUNIKASI TERAPEUTIK DALAM KONSELING ANTARA KONSELOR DAN PASIEN PENYALAHGUNAAN NARKOBADI KLINIK BADAN NARKOTIKA NASIONAL PROVINSI JAWA BARAT - ADRIO KUSMAREZA ADIM; OKI ACHMAD ISMAIL (CoverAge: Journal of Strategic Communication, 2020)
The purpose of this study was to determine Therapeutic Communication in Counseling between Counselors and Drug Abuse Patients. To answer the research objectives, the four focus of the researcher, namely the pre-interaction phase, the orientation phase, the working phase, and the termination phase of Counselor Therapeutic Communication in Rehabilitating Drug Abuse Patients at the National Narcotics Agency Clinic of West Java Province.This study uses qualitative research methods with descriptive studies. The number of informants in this study were four people, consisting of three key informants and one supporting informant. Data collection techniques used in this study are literature study, internet searching, indepth interviews, non-participant observation and documentation.The results of research conducted by the Clinical Counselor of the National Narcotics Board of West Java Province are the pre-interaction phase where the counselor studies patient data. The orientation phase in which the counselor performs the Screening approach and builds trusting relationships with the patient and the Assessment of the counselor ensures patient safety as well as establishes a counseling service plan, and a termination phase where a drug abuse counseling service has been completed and will be referred to post-rehabilitation